(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
This article explores the transformative role of big data analytics in human resources (HR) management, particularly in the context of improving corporate sustainability. This paper discusses the definition of big data and its importance in modern business, emphasizing the volume, velocity, variety, veracity, and value of data. The Industry 4.0 era is underscored, highlighting the importance of up-to-date HR skills and the application of advanced analytics to improve HR processes such as recruitment, retention and employee performance evaluation. This paper discusses how big data analytics facilitates a more objective and data-driven approach to HR decision making, leading to greater efficiency and effectiveness in HR processes. Key technologies such as Hadoop and Apache Spark are mentioned for their ability to manage large-scale data storage and processing. NoSQL database integrations, modern data warehouse solutions, and data visualization tools like Tableau or Power BI were highlighted for their role in helping HR professionals gain actionable insights. The bulk of the paper is dedicated to a literature review, synthesizing findings from various studies on this topic. This review examines the potential of big data in HR to improve the long-term performance and sustainability of companies, also addressing challenges related to privacy and ethical considerations in data handling. The paper concludes by emphasizing the importance of integrating big data analytics in HR management and a focus on sustainability, emphasizing that while challenges exist, the long-term benefits of effectively implementing these technologies are clear: stronger, more adaptive and sustainable business operations.